Political Connection, Auditor Quality, Family Ownership, and Earnings Management: Real and Accrual - Sandy Harianto (Journal of Economics, Business, and Accountancy Ventura, 2022)
This study aims to explore the effect of political connections, external auditor quality, and family ownership on real and discretionary accrual earnings management practices in public companies in Indonesia. So far, previous studies have shown inconclusive and mixed results. The samples used in this study are companies listed on the Indonesia Stock Exchange (IDX) for the last 10 years (2010-2019) prior to the Covid-19 pandemic. The results of this study show that political connections have an effect on reducing both real and discretionary accrual earnings management practices in public companies. High quality external auditors have a significant effect on reducing discretionary accrual earnings management practices only. Meanwhile, the high level of family ownership has an effect on reducing real earnings management practices. The results of this study can be a consideration for public companies to appoint former ministers or high-ranking state officials as company directors or commissioners to suppress earnings management practices.